Improving Balloon Bouquet Making Skills Through the Direct Instruction Model for Deaf Children - Azzahra Firdausi Salma; Zulmiyetri Zulmiyetri; Nurhastuti Nurhastuti; Ardisal Ardisal; Retno Triswandari (Edumaspul: Jurnal Pendidikan, 2024)
One of the skills learned at SLB Muhammadiyah Pauh IX Padang is making balloon bouquets. This is the background to the problems found at the school. This problem arises when the process of learning the skill of making balloon bouquets has not provided maximum results due to the lack of suitability of the learning methods that have been used, namely demonstrations and lectures. This research aims to improve skills in making balloon bouquets through direct instruction. The method used is classroom action research. The research consisted of two cycles. Each cycle consists of four meetings with stages consisting of planning, implementing actions, observing and reflecting. Data collection techniques consist of observation, documentation and tests. The results of the research show 1) the process of learning the skill of making balloon bouquets for deaf children in grades IX and direct instruction. 2) increasing the ability of deaf students in learning balloon bouquet making skills. This can be seen from the comparison of students' scores before being given action, namely IS got a score (50%) and AI (46%). After being given action in cycle I, the capabilities of IS and AI increased with the same score (68%). Then the research continued in cycle II to maximize students' abilities with the final scores obtained by IS (90%) and AI (89%). So it can be concluded that the direct instruction model can improve the skills of deaf students in making balloon bouquets.